Specifics of Knowledge Management in the New Small Organizations - Alexander Lukich Gaponenko; Pavel Sergeevich Myasoyedov (Управленческое консультирование)
In the article, the role of implicit knowledge in success of the modern small organization reveals. Also change in the balance in the modern small organizations between “hard” factors of competitiveness (new technologies, new goods) and “soft” factors among which - knowledge, corporate culture is described. Specific methods of management for creation, development of implicit knowledge and the subsequent management in the small organizations are shown. Among methods is mentioned management on values thanks to which the commitment of employees to the general tasks and trust among collective in the small organizations is cultivated. The trend on increase in number of the small organizations achieving success in a long-term outlook exactly thanks to implicit factors of competitiveness as it is much more difficult to repeat or adopt them in competitive fight is also noted in the article.